2019
DOI: 10.1177/0969141319871977
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent participation in screening for cervical, breast, and bowel cancer in England

Abstract: Objectives To determine how many women participate in all three recommended cancer screening programmes (breast, cervical, and bowel). During their early 60s, English women receive an invitation from all the three programmes. Methods For 3060 women aged 60–65 included in an England-wide breast screening case–control study, we investigated the number of screening programmes they participated in during the last invitation round. Additionally, using the Fingertips database curated by Public Health England, we exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Participants’ familiarity with, and participation in, national screening programmes suggests their enthusiasm for AF screening will not be relevant to all screening invitees. For example, recent studies in the UK found that prior attendance in screening is positively correlated with future participation 41 42. Participants in our study match national trends by being less deprived by practice deprivation status 43.…”
Section: Discussionsupporting
confidence: 64%
“…Participants’ familiarity with, and participation in, national screening programmes suggests their enthusiasm for AF screening will not be relevant to all screening invitees. For example, recent studies in the UK found that prior attendance in screening is positively correlated with future participation 41 42. Participants in our study match national trends by being less deprived by practice deprivation status 43.…”
Section: Discussionsupporting
confidence: 64%
“…A recent study investigated how many women aged 60–65 years (the only group eligible for all three cancer screening programmes in England) participated in all three during their last invitation round 10 . The study revealed that although 90% participated in at least one screening programme, only 35% attended all three.…”
Section: Introductionmentioning
confidence: 99%
“…A relative weakness of this study is that screening tests were not allocated in a random process. However, all comparisons between the 2 screening methods were adjusted for age and deprivation, the 2 principal factors associated with screening attendance and detection of abnormalities 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…However, all comparisons between the 2 screening methods were adjusted for age and deprivation, the 2 principal factors associated with screening attendance and detection of abnormalities. 22,23…”
Section: Strengths and Weaknessesmentioning
confidence: 99%